Protection of Clients’ Rights in the Microcredit Process - M. A. Sadykov (Bulletin of Kharkiv National University of Internal Affairs)
The author has analyzed the role and significance of overdraft for microcredit of the needs of the poor in the conditions of economic crisis and low wages. The positive and negative aspects of overdraft in the context of integration of the country’s financial system into the world community have been clarified. Inconsistency of normative provisions of legislative acts reduces the efficiency of the banking sector of the economy. Bank managers resort to abuse, do not fully explain the terms of microcredit, and do not create conditions for the management of balances and control over them. Customer complaints are considered formally, without their participation. Using the trust of the client, bank managers offer a variety of services in order to receive commissions. The business reputation of a bank employee depends on the amount and amount of funds attracted by the client, but not on the quality of services. It has been offered to strengthen state control over the activities of the banking sector, as well as to increase the legal awareness of young people in the process of using financial services of foreign and domestic banks and credit institutions.